A COMPARATIVE ANALYSIS OF IMPOLITENESS BY PUBLIC FIGURES IN THE SOCIAL NETWORK AND BOHEMIAN RHAPSODY MOVIE - Nefis Farikhatun Nurul Baiti (Program Studi Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
This research examines impoliteness aspects presented in The Social Network and Bohemian Rhapsody movie using pragmatic approach. The objectives of this research are to describe the types of impoliteness strategies addressed by the main characters of both films, to explain the realization of the impoliteness strategies addressed by the main characters of both films, and to compare the results of the impoliteness strategies addressed by the main characters of the films. The method of this research was using descriptive qualitative research. The data were in the form of utterances spoken by the main characters of The Social Network and Bohemian Rhapsody film, while the contexts of the data were dialogues. The researcher used analysis of documents by note-taking to collect the data. Referential analysis was used to analyse the data. From the analysis, the researcher found 44 utterances by the main characters of The Social Network and Bohemian Rhapsody movie. There are 19 utterances (43.2%) utters by the main character of The Social Network film, and 25 utterances (56.8%) utters by the main character of Bohemian Rhapsody film. Which 35 utterances (79.6%) used positive impoliteness strategy, 6 utterances (13.6%) used negative impoliteness strategy, 2 utterances (4.5%) used bald on record impoliteness, and 1 utterance (2.3%) used withhold politeness strategy Keywords: impoliteness, types, realizations, The Social Network, Bohemian Rhapsody